Photo Catalyst Degradation of Methylene Blue Dye by Synthesized TiO2/Graphene Oxides Composites - Mayada Talib Al-Zubaedi (Journal of Global Pharma Technology, 2018)
A ternary nanocomposites of TiO2-Fe2O3/graphene oxide (GO) and TiO2-Fe2O3/reduced graphene oxide (RGO) were prepared from TiO2-Fe2O3 successfully and by precipitation method and graphene oxide (GO) has been prepare from graphite by Hummers method. The ternary nanocomposite possessed enhanced charge separation efficiency. The comparison studied between the three catalysts resulted in the presence of different decomposition data that were affected differently; pH, H2O2, concentration, pollutant concentration, temperature, irradiation time, also the morphology of the ternary nanocomposite and the average diameter which was studied by Atomic Force Microscopy (AFM). The photocatalytic degradation efficiency for methylene blue on the nanocomposites were scanned and the efficiency of photocatalytic degradation of ternary composite was best than that of pure TiO2. Show the result that the photocatalytic efficiency of ternary nanocomposite was obtained and reach 90.8% in 30 min. It is suggested that the ternary composite of TiO2/Fe2O3/RGO can be an efficient multifunctional.Keywords: Photo degradation, TiO2/Fe2O3, composite, Methylene Blue, Fenton's reaction.